Potensi Pengembangan Sport Tourism sebagai Alternatif Media Pembelajaran Pendidikan Jasmani - Indra Jati Kusuma; Panuwun Joko Nurcahyo; Bayu Suko W; Rifqi Festiawan; Ngadiman Ngadiman; Kusnandar Kusnandar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2020)
This study aims to determine the potential of developing sports tourism as an alternative medium for physical education learning. This research is a qualitative descriptive study. Data collection techniques were obtained through observation, focus group discussion, interviews and documentation. Determination of the sample is obtained by purposive sampling technique. Validity test uses data triangulation and data analysis techniques use interactive analysis. The results of the study, 1) the development of tourism carried out are: a) the formation of working groups, b) the arrangement of hill clumps, c) cooperating with youth leaders, d) expanding the network with the community, e) utilizing social media, e) making photo spots, f) impose the price of admission, 2) supporting and inhibiting factors are: supporters: a) there is a spot where the latest photo b) free bicycle lending, c) there are places with interesting natural scenery, d) potential for the development of "down hill" bikes. The obstacles are: a) the source of funds, b) the location is far from water sources, c) the access road to the location is inadequate, d) some areas have started to be damaged, 3) this sports tourism can be developed into a medium of physical education learning because: a) students use as a camping site, b) used as an outbound place, c) encourages student independence through nature, d) fosters a culture of cooperation. In conclusion, sport tourism can be used as an alternative medium for physical education learning. Keywords: Potential; Sport Tourism, Learning Media, Sports Recreation, Sports Tourism